The effect of some medicinal and ornamental plant extracts against Fusarium oxysporum - Sohbat Bahraminejad; Saeed Abbasi; Reza Amiri (Journal of Crop Protection, 2015)
During the past decade, natural plant products as environmentally safe option have received attention for controlling phytopathogenic diseases. Investigation of plants containing natural antimicrobial metabolites for plant protection has been recognized as a desirable method of disease control. The fungus Fusarium oxysporum causes diseases such as root rot, damping off and Fusarium wilt and it infects many plant species and crops. Methanolic crude extracts of 30 plant species belonging to 17 families collected from the west of Iran were screened for antifungal activity against F. oxysporum during 2012. Bioassay of the extracts was conducted by agar dilution method with five replications. The inhibitory effect of the extracts was examined at concentration of 2000 ppm. Twenty out of 30 tested plant species (67%) showed inhibitory activity against mycelial growth of F. oxysporum. The most effective extracts with more than 50% inhibition belonged to Haplophyllum perforatum and Calendula officinalis. High number of plants with antifungal activity in this experiment showed that the flora in the west of Iran could be regarded as a rich source of plants with antifungal activity. Therefore, further screening of other plant species, identifying active fractions or metabolites and in vivo application of active extracts are in progress.